Developmental abnormality induced by strong static magnetic field in Caenorhabditis elegans. Issue 3 (9th March 2015) - Wang, Lei; Du, Hua; Guo, Xiaoying; Wang, Xinan; Wang, Meimei; Wang, Yichen; Wang, Min; Chen, Shaopeng; Wu, Lijun; Xu, An
Abstract : Understanding the effects of strong static magnetic fields (SMFs) on living organisms is significant in health risk assessment, but underlying mechanisms are largely unknown. In the present study, we determined developmental abnormalities induced by 8.5Tesla (T) SMFs in a well‐established in vivo model organism, Caenorhabditis elegans (C. elegans) . Exposure of C. elegans eggs to 8.5 T SMF resulted in a time‐dependent lifespan decrease, whereas only slight changes were observed upon exposure to 5 T SMF. Although SMF exposure did not alter brood size, development rate and stages were significantly modified by 8.5 T SMF. Germ cell apoptosis dramatically increased upon exposure to 8.5 T SMF in adult worms, as confirmed by ced‐3 and ced‐4 mutants, and could be prevented by concurrent treatment with a free radical scavenger, dimethyl sulfoxide. Compared to wild‐type worms, shorter lifespan and greater numbers of apoptotic cells were observed in abnormal methyl viologen sensitivity‐1 ( mev‐1(kn1) ) nematodes with increased sensitivity to oxidative damage. Furthermore, exposure to 8.5 T SMF increased expression of superoxide dismutase‐3 ( sod‐3 ), which is thought to protect against oxidative stress. However, 8.5 T SMF had minimal effects on lifespans of daf‐2 and daf‐16 mutants, which have compromised insulin/IGF‐1 (insulin‐like growth factors‐1) mediated signaling pathways; this finding was consistent with the expression of these genes in wild‐type worms. Our results indicate that developmental toxicity induced by strong SMF in C. elegans is mediated by oxidative stress and may be regulated by the insulin‐like receptor pathway. Bioelectromagnetics. 36:178–189, 2015. © 2015 Wiley Periodicals, Inc.